2008
DOI: 10.1111/j.1399-3089.2008.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of ascending aorta and pulmonary trunk in pigs and humans

Abstract: Our present study suggests that there was no significant difference of elastic properties of ascending aorta and pulmonary trunks between humans and pigs. From biomechanical aspects, anastomosis of corresponding ascending aorta and pulmonary trunks in the process of pig-to-human heart xenotransplantation may be feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Although the mechanical properties of thoracic aortas of young pigs might not exactly match those of elderly people, it has been reported that there was no significant difference in the elastic modulus between the human and pig aorta. 10 Correlations between the ultimate stress and the tangent elastic modulus, and between the ultimate stress and the parameter s r obtained in this study were almost similar for human and porcine aortas (Fig. 8).…”
Section: Feasibility For Estimation Of Ultimate Stresssupporting
confidence: 71%
“…Although the mechanical properties of thoracic aortas of young pigs might not exactly match those of elderly people, it has been reported that there was no significant difference in the elastic modulus between the human and pig aorta. 10 Correlations between the ultimate stress and the tangent elastic modulus, and between the ultimate stress and the parameter s r obtained in this study were almost similar for human and porcine aortas (Fig. 8).…”
Section: Feasibility For Estimation Of Ultimate Stresssupporting
confidence: 71%
“…Second, careful manipulations of the vessel including: the release of the vessel from surrounding fascia and adipose tissue, inserting and firmly securing the catheter within the vessel for long-term lymph collection is critical for successful catheterization. Indeed, it is suggested that the structural integrity of the vessels in neonatal pigs is not as robust as in mature animals and as such can easily tear 39,40 . Using Q-tip applicators to slowly and gently separate fascial layers and fine blunt-ended instruments to pass the suture underneath the vessel greatly reduces the inadvertent puncture or tearing of the lymphatic vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that pig blood vessels have similar behaviour to human blood vessels [24].…”
Section: Discussionmentioning
confidence: 99%